Panorama de la investigacion odontologica peruana en los tiempos del COVID-19 - Quispe-Salcedo, Angela (2020)
The ongoing COVID-19 pandemic has represented a major challenge for human beings during 2020. At time this editorial is written (December 7th) there was a total of 66’422,058 confirmed positive cases and 1’532418 deaths worldwide, according to the World Health Organization (WHO). In our country, the latest report released by the Ministry of Health (MINSA) showed a cumulative of 973,918 confirmed cases including 36,274 deaths. This dramatic scenario has brought various limitations in all aspects of our lives, forcing us to adapt to the “new normality”, which includes strong protection measures to restrain the spread of the viral infection among our population.  Although these restrictions have been progressively lifted with the passing of the months, educational activity at all levels has not yet been reestablished.